2020
DOI: 10.3389/fimmu.2020.00118
|View full text |Cite|
|
Sign up to set email alerts
|

There Is (Scientific) Strength in Numbers: A Comprehensive Quantitation of Fc Gamma Receptor Numbers on Human and Murine Peripheral Blood Leukocytes

Abstract: Antibodies are essential mediators of immunological defense mechanisms, are clinically used as therapeutic agents, but are also functionally involved in various immune-mediated disorders. Whereas IgG antibodies accomplish some of their biological tasks autonomously, many functions depend on their binding to activating and inhibitory Fcγ receptors (FcγR). From a qualitative point of view expression patterns of FcγR on immunologically relevant cell types are well-characterized both for mice and humans. Surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 79 publications
2
72
0
Order By: Relevance
“…In addition, the inhibitory receptor FcγRIIB is expressed on B cells as well as monocytes and macrophages; mouse FcγRIII was described on NK cells, neutrophils, monocytes, and macrophages (31). In addition to relative expression patterns, in a recent comprehensive study using mouse and human peripheral blood, Kerntke et al quantified the number of cell surface FcγR on derived immune cells including potential APCs such as B cells and monocytes (39). The authors found that on human monocytes, more FcγRIIA molecules were expressed compared to FcγRIIB.…”
Section: Overview Of Fcγrs and Igg Bindingmentioning
confidence: 99%
“…In addition, the inhibitory receptor FcγRIIB is expressed on B cells as well as monocytes and macrophages; mouse FcγRIII was described on NK cells, neutrophils, monocytes, and macrophages (31). In addition to relative expression patterns, in a recent comprehensive study using mouse and human peripheral blood, Kerntke et al quantified the number of cell surface FcγR on derived immune cells including potential APCs such as B cells and monocytes (39). The authors found that on human monocytes, more FcγRIIA molecules were expressed compared to FcγRIIB.…”
Section: Overview Of Fcγrs and Igg Bindingmentioning
confidence: 99%
“…FcγRIIa is widely expressed on innate immune cells (including neutrophils and both monocyte subsets). These cell types may also express the closely related inhibitory FcγRIIb (95,96). This further complicates interpretation of data because of high homology of the extracellular domains.…”
Section: Fcγriiamentioning
confidence: 99%
“…Glycosylation of IgG molecules is essential for its binding with all receptors through the maintenance of an open conformation of the two heavy chains, whereas deglycosylated IgG antibodies are unable to mediate the inflammatory response triggered in vivo. A therapeutic application of gamma globulins intravenously indicates how these acts as anti-inflammatory [55].…”
Section: Immunity and Inflammationmentioning
confidence: 99%